Monolithic integration of four-colour InGaN-based nanocolumn LEDs - Kishino, K; Yanagihara, A; Ikeda, K; Yamano, K (Electronics letters, 2015)
The monolithic integration of four-colour indium gallium nitride (InGaN)-based nanocolumn light-emitting diodes (LEDs) is demonstrated. In the integrated nanocolumn LED unit, blue-, sky-blue-, green- and yellow-emitting micro-LEDs (LEDs 1–4) with a 65 μm diameter circular indium tin oxide emission window were arrayed in a 2 × 2 square lattice with a lattice constant of 190 μm. LEDs 1–4 consisted of nanocolumn arrays arranged in a triangular lattice with a lattice constant of 300 nm and their nanocolumn diameters at the position of the InGaN/gallium nitride (GaN) multiple quantum wells (MQWs) were 119, 145, 188 and 231 nm, respectively. The increase in nanocolumn diameter from LED 1 to LED 4 resulted in increasing emission peak wavelengths, which were 465, 489, 510 and 570 nm for LEDs 1–4, respectively. On the same substrate, a red-emitting micro-LED was prepared, in which the nanocolumn diameter was increased to 260 nm by using a 350 nm-lattice-constant nanocolumn array. A combination of different lattice constants in an integrated LED unit is expected to contribute to the achievement of red–green–blue–yellow (RGBY)-colour-integrated nanocolumn LEDs.